Design frameworks: a study of Kansas City's Power & Light District - Tucker, Tyler (Kansas State University, 2017)
The Power & Light District is a mixed-use, urban district in the heart of the central business district. The area has seen rapid revitalization since construction began in 2005, and become a popular destination. This project examined the area using a chosen design framework. Documentation and reflection on the application of the design framework was then used to judge its efficacy when applied at the district scale. To gain the desired outcome of this study, there is a two-part research question. 1. How is Kansas City, Missouri’s Power & Light District viewed, and how well does the district score, when using the design framework created in Re-Framing Urban Space: Urban Design for Emerging Hybrid and High-Density Conditions? 2. How well does the Re-Framing Urban Space: Urban Design for Emerging Hybrid and High-Density Conditions design framework work when applied to the Power & Light District in Kansas City, Missouri? This project used several methods to research design frameworks and the Power & Light District. The literature review studies urban design and several design frameworks. GIS diagrams were used to study the Power & Light District. On-site surveys were used to provide public input. Finally, the chosen design framework was used to score the area. Documentation on the use of the design framework was used to reflect on the design framework’s efficacy. Chapter 4 Results and Chapter 5 Conclusions show the application of the design framework to the Power & Light District, and reflections on the efficacy of the framework. The district scores very well with an urban space value of 77%. While the design framework is very extensive, it is meant to judge sites at a smaller scale. For a more accurate scoring of the Power & Light District, the design framework could be adapted to better judge sites at a district scale.
Keywords: Landscape architecture; Urban design; Design frameworks; Power & Light District